A SYSTEMATIC REVIEW OF PROJECT-BASED LEARNING IMPLEMENTATION IN THE MERDEKA CURRICULUM - Fitri Shofi Nur Iman; Annisa Fauziah (Jurnal Intelek Dan Cendikiawan Nusantara, 2025)
The implementation of the Merdeka Curriculum emphasizes flexible, contextual, and learner-centered learning with the aim of developing 21st-century competencies and realizing the Pancasila Student Profile. Project-Based Learning (PjBL) is one of the approaches recommended in this curriculum because it provides opportunities for students to learn through authentic projects that involve collaboration, creativity, and direct problem solving. This study aims to review the effectiveness of PjBL implementation in the Merdeka Curriculum and identify the benefits and obstacles found at various levels of education in Indonesia. The method used is a Systematic Literature Review (SLR) following the PRISMA guidelines through searching articles in the Google Scholar, Eric, and Mendeley databases, then selecting 15 articles published in 2020–2025 that meet the inclusion criteria. The results of the study show that PjBL is able to increase student engagement in the cognitive, affective, and psychomotor domains, as well as support character development, communication, critical thinking skills, and creativity. However, its implementation still faces challenges such as limited facilities, teacher readiness as facilitators, project time management, and difficulties in authentic assessment. Therefore, PjBL has great potential in supporting the success of the Merdeka Curriculum and needs to be strengthened through teacher training and the provision of adequate supporting facilities so that its implementation is equitable and sustainable